Factors associated with statural growth in pediatric kidney transplant recipients with focus on metabolic acidosis - Prytula, Agnieszka; Reynders, Dries; Goetghebeur, Els; Krupka, Kai; Bacchetta, Justine; Kanzelmeyer, Nele; Guzzo, Isabella; Labbadia, Raffaella; Benetti, Elisa; Shenoy, Mohan; Sellier-Leclerc, Anne-Laure; Oh, Jun; et al. (Pediatric nephrology, 2025)
We investigated factors associated with post-transplant growth in pediatric kidney transplant (KTx) recipients with a focus on plasma bicarbonate (HCO3−) and estimated the effect of alkali treatment on growth.